PENGEMBANGAN KOMPONEN TUJUAN DALAM PENGEMBANGAN KURIKULUM PAI MULTIKULTURAL - Saymsul Rijal; Moh Afiful Khair; Jamiliya Susantin (Dewan Pendidikan Pamekasan, 2023)
Multicultural-based Islamic education is interpreted as an Islamic education process that has the principles of democracy, equality, and justice, is oriented towards humanity, togetherness, and peace, and develops attitudes: recognizing, accepting, and respecting diversity based on the Al-Qur'an and the Hadith of the Prophet SAW. This process is realized in the form of educational planning, implementation, and evaluation. The development of a multicultural objective component in Islamic religious education aims to produce a better understanding of Islam as an inclusive religion, promote interfaith harmony, and form students who are tolerant, open, and appreciate diversity in society. Multicultural-based curriculum development must be based on culture in developing the curriculum. This emphasis on diversity also applies to Islamic religious education which is always required to be able to answer all the problems that exist in this modern era. Thus, it is the noble duty of an Islamic teacher to try to answer this problem by developing a multicultural-based curriculum in Islamic Religious Education. The characteristics of a curriculum based on multiculturalism can be reflected in learning to live with differences, building mutual trust, understanding each other, upholding mutual respect, inclusion, appreciation and interdependence, conflict resolution, and non-violent reconciliation. Meanwhile, the multicultural-based PAI curriculum aims to expose students to various challenges, threats, obstacles, or disturbances faced in social life. To build inclusive diversity in schools, several Islamic religious education materials can be developed with multicultural nuances, including the Qur'an, Fiqh, Aqidah, and History.